Complex longitudinal diversification across South China and Vietnam in Stejneger's pit viper, Viridovipera stejnegeri (Schmidt, 1925) (Reptilia: Serpentes: Viperidae). Issue 12 (21st May 2016) - Guo, Peng; Liu, Qin; Zhu, Fei; Zhong, Guang H.; Chen, Xin; Myers, Edward A.; Che, Jing; Zhang, Liang; Ziegler, Thomas; Nguyen, Truong Q.; Burbrink, Frank T.
Abstract: Viridovipera stejnegeri is one of the most common pit vipers in Asia, with a wide distribution in southern China and Vietnam. We investigated historical demography and explored how the environment and climatic factors have shaped genetic diversity and the evolutionary history of this venomous snake. A total of 171 samples from 47 localities were sequenced and analysed for two mitochondrial gene fragments and three nuclear genes. Gene trees reveal the existence of two well‐supported clades (Southwest China and Southeast China) with seven distinct and strongly supported, geographically structured subclades within V. stejnegeri . Estimation of divergence time and ancestral area suggests that V. stejnegeri originated at ~6.0 Ma in the late Miocene on the Yunnan–Guizhou Plateau. The estimated date of origin and divergence of the island populations of Taiwan and Hainan closely matches the geological origin of the both islands. The mtDNA gene tree reveals the presence of west–east diversification in V. stejnegeri populations. Complex orogenesis and heterogeneous habitats, as well as climate‐mediated habitat differentiation including glacial cycles, all have influenced population structure and the distribution of this taxon. The validity of V. stejnegeri chenbihuii is questionable, and this subspecies most probably represents an invalid taxon.